Konstruksi Sosial Sinamot sebagai Mahar dalam Perkawinan Masyarakat Suku Batak Toba di Kota Jakarta Timur - Sagala, Citra Ayu; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
The kinship solidarity of the Toba Batak tribe is a dalihan na tolu consisting of: hula-hula, dongan sabutuha, and boru. Marriage by applying the concept of the tradition sinamot carried out by the Toba Batak tribe in East Jakarta is a preservation of traditional culture in the midst of the modernization of the capital city. Along with the development of the times and the influence of the existence of the Toba Batak people in the East Jakarta City area, the amount of sinamot in traditional marriages can be categorized according to education, occupation, background, social status, and so on. Batak Toba youth in East Jakarta City who have good finances will certainly find it easier to carry out traditional marriages or apply the tradition sinamot compared to youths who do not have good finances. Keywords: Sinamot, social construction, Batak Toba people